2018
DOI: 10.1177/1063426618763108
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of IEP Accommodations for Secondary Students With Emotional and Behavioral Problems

Abstract: Accommodations are intended to address student academic and behavioral deficits by reducing obstacles that impede learning and accurately measuring skills. There is limited research, however, pertaining to the types of accommodations students receive and their selection, particularly among those with emotional and behavioral problems. This is a significant concern for secondary age students who spend the majority of their day in regular education settings and must participate in high-stakes testing. We examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…One example of school medicalized social control is the enrollment of children with behavior problems in behavioral individualized education plans (IEPs) designed to accommodate the needs of children with medically diagnosed behavior problems (Kim et al, ; Lavin, ; Ramey, ). For example, children who are diagnosed with ADHD and report being easily distracted or having difficulty staying on task are provided extra time to take their exams, often in separate rooms (Danneker & Bottge, ; Kern et al ). Another important feature of behavioral IEPs is that schools are required to hold manifestation determination hearings if students with a limiting disability faces suspension or expulsion (Katsiyannis & Maag, ).…”
Section: Conceptualizing Medicalized Child Social Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…One example of school medicalized social control is the enrollment of children with behavior problems in behavioral individualized education plans (IEPs) designed to accommodate the needs of children with medically diagnosed behavior problems (Kim et al, ; Lavin, ; Ramey, ). For example, children who are diagnosed with ADHD and report being easily distracted or having difficulty staying on task are provided extra time to take their exams, often in separate rooms (Danneker & Bottge, ; Kern et al ). Another important feature of behavioral IEPs is that schools are required to hold manifestation determination hearings if students with a limiting disability faces suspension or expulsion (Katsiyannis & Maag, ).…”
Section: Conceptualizing Medicalized Child Social Controlmentioning
confidence: 99%
“…Although individualized behavior plans are specific to the needs of certain students, they are effective at providing social control in schools. First, many behavioral IEPs ensure that children with behavior problems receive extra adult supervision, often in the form of a counselor or special education professional (Kern et al ). This extra adult supervision minimizes the chances for children with behavior problems to disrupt the classroom and discourages other children from acting out as well (Gottfredson & DiPietro, ).…”
Section: Conceptualizing Medicalized Child Social Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The services targeted in these documents are also imprecise. For example, researchers examining IEPs for students with emotional and behavioral problems found that specific accommodations were rarely matched to the stated student needs [11]. Based on such findings, it seems safe to conclude that special education offers one school-based mechanism to address individual student needs, but practices can vary considerably based on local knowledge, skills, and resources.…”
Section: Special Educationmentioning
confidence: 99%
“…Recent research finds that the vast majority of students with disabilities receive accommodations, and it appears that accommodations are more frequently recommended and implemented than evidence-based interventions are. Kern et al (2019) inspected the special education plans (IEP documents) of 222 students in secondary school, most of whom had diagnoses of a learning disability, an emotional/ behavioral disorder, or a health impairment. Collectively, the IEP documents listed 1,840 accommodations for these students.…”
Section: Introductionmentioning
confidence: 99%